Pengaruh Kepemimpinan dan Pengawasan terhadap Kinerja Pegawai di Kantor Kecamatan Tugumulyo Kabupaten Musi Rawas - Irma Idayati; Hardi Mulyono (IPM2KPE, 2020)
This study aims to learn about Leadership and Supervision of Employee Performance at the Tugumulyo District Office in Musi Rawas Regency. The research method used in this research is quantitative research. The results of the study using multiple regression results the coefficient of determination (R2) of 47.7% means, leadership and supervision have an effect of 47.7%, while 52.3% is needed by other variables. Fcount = 12,300> F table = 3.32. Value, the Fcount value is greater than the Fable value. Conclusion, there is a significant leadership between Leadership and Supervision of Employee Performance in the Tugumulyo District Office in the Musi Rawas Office. Keywords: Leadership, Performance, Supervision